Differential Effects of Saikosaponins A, B2, B4, C and D on Alcohol and Chocolate Self-Administration in Rats. (22nd May 2020) - Maccioni, Paola; Lorrai, Irene; Fara, Federica; Carai, Mauro A M; Gessa, Gian Luigi; Chin, Young-Won; Lee, Jung Hwan; Kwon, Hak Cheol; Corelli, Federico; Colombo, Giancarlo
Abstract: Aims: Treatment with saikosaponin A (SSA)—an ingredient of the medicinal herb, Bupleurum falcatum —has been reported to suppress several addictive-like behaviors, including morphine, cocaine, alcohol and chocolate self-administration in male rats. The aim of this investigation was to investigate whether saikosaponins of B. falcatum other than SSA affect alcohol and chocolate self-administration in rats. Methods: Ovariectomized female Sardinian alcohol-preferring (sP) and Wistar rats were trained to self-administer alcohol (15%, v/v) and a chocolate solution [5% (w/v) Nesquik® in water], respectively, under fixed ratio schedules of reinforcement. The following saikosaponins were compared to SSA: saikosaponin D (SSD; epimer of SSA), saikosaponin C (SSC), saikosaponin B2 (SSB2 ) and saikosaponin B4 (SSB4 ). All saikosaponins were tested acutely at the doses of 0, 0.25, 0.5 and 1 mg/kg (i.p.). Results: Treatment with SSA and SSD resulted in highly similar, marked reductions in alcohol self-administration; SSC failed to alter lever-responding for alcohol, while SSB2 and SSB4 produced intermediate reductions. Only SSA and SSD reduced chocolate self-administration, with SSC, SSB2 and SSB4 being ineffective. Conclusions: The wide spectrum of efficacy of saikosaponins in reducing alcohol and chocolate self-administration suggests that even relatively small structural differences are sufficient to produce remarkable changes in their in vivo pharmacological profile. Together, these results confirm that roots of B. falcatum may be an interesting source of compounds with anti -addictive potential. Abstract : Saikosaponins, including saikosaponin A (SSA), are active ingredients of the Asian medicinal herb, Bupleurum falcatum . SSA is known to suppress alcohol, cocaine, morphine and chocolate self-administration in rats. Testing multiple saikosaponins, we found that small structural changes resulted in markedly different effects on alcohol and chocolate self-administration in rats.